Menopausal hormone therapy use and long‐term all‐cause and cause‐specific mortality in the Long Island Breast Cancer Study Project. Issue 12 (30th July 2020) - Wang, Tengteng; Bradshaw, Patrick T.; Moorman, Patricia G.; Nyante, Sarah J.; Nichols, Hazel B.; Shantakumar, Sumitra; Parada, Humberto; Khankari, Nikhil K.; Terry, Mary Beth; Teitelbaum, Susan L.; Neugut, Alfred I.; Gammon, Marilie D.
Abstract: Previous studies have observed a reduced mortality risk associated with menopausal hormone therapy (MHT) use among breast cancer survivors. We sought to clarify whether such association could be explained by tumor heterogeneity, specific causes of death, confounding from comorbidities or health behaviors, and a comparison group of women without breast cancer. We interviewed 1508 women newly diagnosed with first primary breast cancer in 1996 to 1997 ( 3 months after diagnosis), and 1556 age‐matched women without breast cancer, about MHT use history. The National Death Index was used to ascertain vital status after a median of 17.6 years of follow‐up (N = 597 deaths for breast cancer subjects). Multivariable‐adjusted Cox proportional hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (95%CIs) for all‐cause mortality, and cause‐specific HR (cHR) for breast cancer and cardiovascular disease (CVD). The Fine‐Gray model was used to account for competing causes of death. Among women with breast cancer, ever vs never MHT use was inversely associated with all‐cause (HR = 0.77, 95%CI = 0.62‐0.95), breast cancer‐specific (cHR = 0.69, 95%CI = 0.48‐0.98), and CVD‐specific mortality (cHR = 0.57, 95%CI = 0.38‐0.85). Difference of the association was observed in breast cancer‐specific mortality according to hormone receptor status (negative tumors: cHR = 0.44, 95%CI = 0.19‐1.01; positive tumors: cHR = 0.96, 95%CI = 0.60‐1.53). Among the comparison group, we observed similar, but more modest inverse associations for all‐cause and CVD‐specific mortality. MHT use was inversely associated with mortality after breast cancer, even after accounting for competing causes of death and multiple confounders, and was evident among women without breast cancer. Potential heterogeneity by hormone receptor status requires more study. Abstract : What's new? The Women's Health Initiative trial found that menopausal hormone therapy (MHT) is associated with an increased risk of breast cancer and cardiovascular disease (CVD). Does the same association hold for MHT and mortality rates? In the present study, the authors found quite the opposite—that MHT use history was associated with decreased mortality, both in women diagnosed with breast cancer, and in a comparison group without breast cancer. This inverse association applied even after accounting for confounding variables and competing causes of death. This is an optimistic finding for women who have used MHT, especially for breast cancer survivors.